1996
DOI: 10.1177/08959374960100021401
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Localization of Amelogenin in the Rat Incisor

Abstract: Gene expression and localization of amelogenin were studied in the developing rat incisor by the methods of in situ hybridization and immunohistochemistry. ISH revealed the first expression of amelogenin mRNA in the inner enamel epithelium of the cervical loop. The signals were clearly observed in pre-ameloblasts in the region bordering on predentin formation and became more intense toward the cells on the initial enamel matrix secretion. The maximal signals were found in the cytoplasm of secretory ameloblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Using the probe generated from bovine amelogenin cDNA coding for exons 1-7 (Shimokawa et al 1987a), Inage et al (1996) showed a precise mapping of amelogenin mRNA expression in rat incisor. In their studies the amelogenin mRNA signals started to appear in the cells of the inner enamel epithelium close to the preameloblasts and lasted until the ameloblasts entered the initial stage of enamel maturation, although the signal expression became weaker during the transitional stage.…”
Section: Discussionmentioning
confidence: 99%
“…Using the probe generated from bovine amelogenin cDNA coding for exons 1-7 (Shimokawa et al 1987a), Inage et al (1996) showed a precise mapping of amelogenin mRNA expression in rat incisor. In their studies the amelogenin mRNA signals started to appear in the cells of the inner enamel epithelium close to the preameloblasts and lasted until the ameloblasts entered the initial stage of enamel maturation, although the signal expression became weaker during the transitional stage.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are not consistent with a relationship to the onset of apoptosis. The weak signal observed at the beginning of postsecretory transition may be related to secretory activity because ameloblasts at this stage in the rat incisor still synthesize matrix proteins, albeit at a much reduced rate (Smith 1984;Nanci et al 1987Nanci et al , 1998Inage et al 1996). With regard to the relatively similar immunolabeling signal for IGF-IIR across amelogenesis, the finding is surprising because the lysosomal pool of ameloblasts rapidly expands in preparation for the secretory stage and then gradually enlarges through secretory and into the maturation zone (Smith 1984).…”
Section: The Journal Of Histochemistry and Cytochemistrymentioning
confidence: 99%
“…Several investigations of rodent incisor and molar tooth germs have shown that not only secretory ameloblasts but also maturation ameloblasts express amelogenins (Nanci et al 1987;DenBesten and Li 1992;Fong et al 1996;Inage et al 1996;Wurtz et al 1996;Karg et al 1997). However, it was not clear that maturation ameloblasts of porcine tooth germs express amelogenins.…”
Section: Introductionmentioning
confidence: 95%